A high thermal conductivity silicon nitride ceramic material and preparation method thereof

CN119330722BActive Publication Date: 2025-03-07HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411908921.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-07
Estimated Expiration
2044-12-24

Smart Images

  • Figure CN119330722B_ABST
    Figure CN119330722B_ABST
Patent Text Reader

Abstract

The invention relates to the field of ceramic materials, in particular to a high thermal conductivity silicon nitride ceramic material and a preparation method thereof. The silicon nitride ceramic material contains in-situ generated aluminum nitride nanowires and is prepared from the following raw materials in parts by weight: 80-100 parts of silicon nitride, 5-10 parts of silicon nitride magnesium, 5-10 parts of yttrium oxide, 1-5 parts of fluoride, 1-3 parts of aluminum isopropoxide, and 10-20 parts of a binder. Tests show that the silicon nitride ceramic material prepared by the invention has high mechanical strength and excellent thermal conductivity. As a ceramic substrate material, the silicon nitride ceramic material can meet the application requirements of high calorific value and large thermal strain of future semiconductor devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic materials, in particular to a high thermal conductivity silicon nitride ceramic material and a preparation method thereof. Background Art

[0002] High-power semiconductor devices have a development trend of high voltage, high current and high power density, which puts higher requirements on the heat dissipation capacity and reliability of the ceramic substrate in the device. Silicon nitride ceramics with high thermal conductivity and excellent mechanical properties have attracted widespread attention as the preferred heat dissipation substrate material for power semiconductor devices. How to prepare silicon nitride ceramic materials with higher thermal conductivity to meet the application requirements of high heat generation and large thermal strain of future semiconductor devices has become a research hotspot for scientific researchers. Summary of the invention

[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a high thermal conductivity silicon nitride ceramic material and a preparation method thereof.

[0004] The technical solutions adopted are as follows:

[0005] A high thermal conductivity silicon nitride ceramic material containing in-situ generated aluminum nitride nanowires;

[0006] The high thermal conductivity silicon nitride ceramic material is prepared from the following raw materials in parts by weight:

[0007] 80-100 parts of silicon nitride, 5-10 parts of magnesium silicon nitride, 5-10 parts of yttrium oxide, 1-5 parts of fluoride, 1-3 parts of aluminum isopropoxide, and 10-20 parts of a binder;

[0008] The binder is a polyvinyl alcohol grafted triazine isocyanate solution.

[0009] Furthermore, the fluoride consists of ammonium fluoride and magnesium fluoride.

[0010] Furthermore, the mass ratio of ammonium fluoride to magnesium fluoride is 1-5:1-5.

[0011] Furthermore, the mass concentration of the polyvinyl alcohol grafted triazine isocyanate solution is 5-10%.

[0012] Furthermore, the preparation method of the polyvinyl alcohol grafted triazine isocyanate solution is as follows:

[0013] Dissolve polyvinyl alcohol in DMF, add triazine isocyanate and organotin catalyst, stir and mix, react the obtained reaction solution in a water bath at 40-60°C for 5-10h, remove DMF by vacuum distillation after the reaction, finally add anhydrous ethanol and mix to obtain a solution of corresponding mass concentration.

[0014] Furthermore, the triazine isocyanate is a product in which an isocyanate group replaces a hydrogen atom on triazine, and specifically may be 1,3,5-triazine-2-isocyanate (CAS: 388566-39-0).

[0015] The organic tin catalyst is a metal organic compound formed by direct combination of tin and carbon elements, and specifically can be any one of dibutyltin dilaurate, stannous octoate, dibutyltin diacetate, and dibutyltin didodecylsulfide, or a combination of two or more thereof.

[0016] Furthermore, the mass ratio of the polyvinyl alcohol to the triazine isocyanate is 50-100:1, and the grafting rate is controlled by controlling the mass ratio of the polyvinyl alcohol to the triazine isocyanate, thereby controlling the granulation effect.

[0017] The present invention also provides a method for preparing a high thermal conductivity silicon nitride ceramic material:

[0018] Silicon nitride, magnesium silicon nitride, yttrium oxide and fluoride are mixed and ball-milled, and then dried to obtain a first mixed powder; the first mixed powder is then mixed and ball-milled with aluminum isopropoxide under nitrogen protection, and then dried to obtain a second mixed powder; the second mixed powder is mixed with a binder to form granules; the obtained granules are added to a mold and pressed into a green body; the green body is placed in a sintering furnace, and nitrogen with a pressure of 1-10MPa is introduced for protection; the temperature is first raised to 500-600°C for pre-sintering for 1-5h, and then the temperature is raised to 1500-1700°C for sintering for 1-5h.

[0019] Furthermore, the speed of the first stage heating is 1-5°C / min, and the speed of the second stage heating is 10-20°C / min.

[0020] Beneficial effects of the present invention:

[0021] The invention provides a high thermal conductivity silicon nitride ceramic material. The aluminum nitride nanowires generated in situ inside the material improve the mechanical strength of the silicon nitride ceramic material through nano-size effects, including strengthening of nano-grain boundaries, crack tip effects and nano-phase changes. Moreover, the aluminum nitride nanowires form a heat conduction path inside the material, so that heat can be more effectively transferred during the heat conduction process, thereby improving the mechanical strength and thermal conductivity of the silicon nitride ceramic material. Fluoride can reduce the temperature and viscosity of liquid phase formation, promote sintering densification, and can also be used as a supplement of nitrogen source to promote the generation of aluminum nitride nanowires. Aluminum isopropoxide is used as an aluminum source, and polyvinyl alcohol grafted triazine isocyanate is used as an organic binder. The triazine group in its structure has a high nitrogen content, which can provide a nitrogen source for the growth of aluminum nitride nanowires. After testing, the silicon nitride ceramic material prepared by the invention has high mechanical strength and excellent thermal conductivity. As a ceramic substrate material, it can meet the application requirements of high heat generation and large thermal strain of future semiconductor devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the cross section of the silicon nitride ceramic material prepared in Example 1. DETAILED DESCRIPTION

[0023] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0024] Embodiment 1:

[0025] A high thermal conductivity silicon nitride ceramic material is prepared from the following raw materials in parts by weight:

[0026] 90 parts of silicon nitride, 8 parts of silicon magnesium nitride, 6 parts of yttrium oxide, 1 part of ammonium fluoride, 1 part of magnesium fluoride, 2 parts of aluminum isopropoxide, and 18 parts of a binder.

[0027] Wherein, the binder is a polyvinyl alcohol grafted triazine isocyanate solution, and the specific preparation method is as follows:

[0028] Dissolve 88g of polyvinyl alcohol in 500ml of DMF, then add 1.22g of 1,3,5-triazine-2-isocyanate and 0.05g of dibutyltin dilaurate, stir mechanically and mix well, react the obtained reaction solution in a 60°C water bath for 8h, remove DMF by reduced pressure distillation after the reaction, finally add anhydrous ethanol and mix mechanically to prepare a solution with a mass concentration of 8%.

[0029] Preparation method of the above-mentioned high thermal conductivity silicon nitride ceramic material:

[0030] Silicon nitride, magnesium silicon nitride, yttrium oxide and fluoride are added to the ball mill of a planetary ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 10 hours and then dried to obtain a first mixed powder. The first mixed powder and aluminum isopropoxide are added to the ball mill of a planetary ball mill under nitrogen protection, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 1 hour and then vacuum dried to obtain a second mixed powder. The second mixed powder is mixed with a binder to form granules. The obtained granules are passed through an 80-mesh sieve and added to a mold and pressed into a green body at 50 MPa. The green body is placed in a sintering furnace and nitrogen at a pressure of 2 MPa is introduced for protection. The temperature is first increased to 600°C at a rate of 1°C / min and pre-sintered for 5 hours, and then increased to 1650°C at a rate of 10°C / min and sintered for 3 hours. The cross section is observed using a SUPRA 55 SAPPHIRE scanning electron microscope, see Figure 1 , it can be seen that there are "bridging" aluminum nitride nanowires.

[0031] Embodiment 2:

[0032] A high thermal conductivity silicon nitride ceramic material is prepared from the following raw materials in parts by weight:

[0033] 100 parts of silicon nitride, 5 parts of silicon magnesium nitride, 10 parts of yttrium oxide, 1 part of ammonium fluoride, 1 part of magnesium fluoride, 1 part of aluminum isopropoxide, and 20 parts of a binder.

[0034] Wherein, the binder is a polyvinyl alcohol grafted triazine isocyanate solution, and the preparation method is the same as that of Example 1;

[0035] Preparation method of the above-mentioned high thermal conductivity silicon nitride ceramic material:

[0036] Silicon nitride, magnesium silicon nitride, yttrium oxide and fluoride are added to the ball mill of a planetary ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 10 hours and then dried to obtain a first mixed powder. The first mixed powder and aluminum isopropoxide are added to the ball mill of a planetary ball mill under nitrogen protection, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 1 hour and then vacuum dried to obtain a second mixed powder. The second mixed powder is mixed with a binder to form granules. The obtained granules are passed through an 80-mesh sieve and added to a mold and pressed into a green body at 50 MPa. The green body is placed in a sintering furnace, and nitrogen at a pressure of 2 MPa is introduced for protection. The temperature is first increased to 600°C at a rate of 1°C / min and pre-sintered for 5 hours, and then the temperature is increased to 1700°C at a rate of 10°C / min and sintered for 3 hours.

[0037] Embodiment 3:

[0038] A high thermal conductivity silicon nitride ceramic material is prepared from the following raw materials in parts by weight:

[0039] 100 parts of silicon nitride, 10 parts of silicon magnesium nitride, 10 parts of yttrium oxide, 1 part of ammonium fluoride, 1 part of magnesium fluoride, 3 parts of aluminum isopropoxide, and 20 parts of a binder.

[0040] Wherein, the binder is a polyvinyl alcohol grafted triazine isocyanate solution, and the preparation method is the same as that of Example 1;

[0041] Preparation method of the above-mentioned high thermal conductivity silicon nitride ceramic material:

[0042] Silicon nitride, magnesium silicon nitride, yttrium oxide and fluoride are added to the ball mill of a planetary ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 10 hours and then dried to obtain a first mixed powder. The first mixed powder and aluminum isopropoxide are added to the ball mill of a planetary ball mill under nitrogen protection, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 1 hour and then vacuum dried to obtain a second mixed powder. The second mixed powder is mixed with a binder to form granules. The obtained granules are passed through an 80-mesh sieve and added to a mold and pressed into a green body at 50 MPa. The green body is placed in a sintering furnace, and nitrogen at a pressure of 2 MPa is introduced for protection. The temperature is first increased to 600°C at a rate of 1°C / min and pre-sintered for 5 hours, and then the temperature is increased to 1600°C at a rate of 10°C / min and sintered for 3 hours.

[0043] Embodiment 4:

[0044] A high thermal conductivity silicon nitride ceramic material is prepared from the following raw materials in parts by weight:

[0045] 80 parts of silicon nitride, 5 parts of silicon magnesium nitride, 5 parts of yttrium oxide, 1 part of ammonium fluoride, 1 part of magnesium fluoride, 1 part of aluminum isopropoxide, and 15 parts of a binder.

[0046] Wherein, the binder is a polyvinyl alcohol grafted triazine isocyanate solution, and the preparation method is the same as that of Example 1;

[0047] Preparation method of the above-mentioned high thermal conductivity silicon nitride ceramic material:

[0048] Silicon nitride, magnesium silicon nitride, yttrium oxide and fluoride are added to the ball mill of a planetary ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 10 hours and then dried to obtain a first mixed powder. The first mixed powder and aluminum isopropoxide are added to the ball mill of a planetary ball mill under nitrogen protection, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 1 hour and then vacuum dried to obtain a second mixed powder. The second mixed powder is mixed with a binder to form granules. The obtained granules are passed through an 80-mesh sieve and added to a mold and pressed into a green body at 50 MPa. The green body is placed in a sintering furnace, and nitrogen at a pressure of 2 MPa is introduced for protection. The temperature is first increased to 600°C at a rate of 1°C / min and pre-sintered for 5 hours, and then the temperature is increased to 1550°C at a rate of 10°C / min and sintered for 3 hours.

[0049] Comparative Example 1:

[0050] The process is substantially the same as Example 1, except that no ammonium fluoride is added.

[0051] Comparative Example 2:

[0052] The process is basically the same as Example 1, except that aluminum isopropoxide is not added.

[0053] Comparative Example 3:

[0054] The process is basically the same as Example 1, except that the polyvinyl alcohol grafted triazine isocyanate solution is replaced by a polyvinyl alcohol ethanol solution of the same concentration.

[0055] Performance Test:

[0056] The silicon nitride ceramic materials in Examples 1-4 and Comparative Examples 1-3 were made into samples for performance testing;

[0057] The three-point bending strength of the sample was tested using a SANS-CMT5104A universal testing machine. The sample size was 3 mm × 4 mm × 20 mm and the loading rate was 0.5 mm min. -1 The thermal diffusivity of the sample was measured by LFA-457 laser thermal conductivity analyzer, and its thermal conductivity (λ: W·m -1 ·K -1 ) is calculated by the following formula:

[0058] λ = α c p ·ρ

[0059] Where: α is the thermal diffusion coefficient, c p is the isobaric specific heat capacity, ρ is the bulk density of the sample;

[0060] The test results are shown in Table 1 below:

[0061] ;

[0062] It can be seen from Table 1 above that the silicon nitride ceramic material prepared by the present invention has high mechanical strength and excellent thermal conductivity;

[0063] Ammonium fluoride is not only used as a sintering aid, but also as a supplement to the nitrogen source. By comparing the data of Example 1 with that of Comparative Example 1, it can be seen that the addition of ammonium fluoride plays a positive role in improving the mechanical strength and thermal conductivity of silicon nitride ceramic materials.

[0064] Aluminum isopropoxide is used as an aluminum source. After being added, aluminum nitride nanowires are generated in situ. The aluminum nitride nanowires improve the mechanical strength of the silicon nitride ceramic material through nano-size effects, including strengthening of nano-grain boundaries, crack tip effects, and nano-phase transformations. In addition, the aluminum nitride nanowires form a heat conduction path inside the aluminum nitride ceramic material, so that heat can be transferred more effectively during the heat conduction process. This can be confirmed by comparing the data of Example 1 with that of Comparative Example 2.

[0065] On the one hand, the polyvinyl alcohol grafted triazine isocyanate solution acts as an organic binder, and on the other hand, the triazine group has a high nitrogen content, which can provide a nitrogen source for the growth of aluminum nitride nanowires. When polyvinyl alcohol is used instead of polyvinyl alcohol grafted triazine isocyanate, only ammonium fluoride can provide a nitrogen source, and the generated aluminum nitride nanowires are reduced, resulting in a decrease in the mechanical strength and thermal conductivity of the silicon nitride ceramic material, which can be confirmed by comparing the data of Example 1 with Comparative Example 3.

[0066] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high thermal conductivity silicon nitride ceramic material, characterized in that: It contains aluminum nitride nanowires generated in situ; The invention is prepared from the following raw materials in parts by weight: 80-100 parts of silicon nitride, 5-10 parts of magnesium silicon nitride, 5-10 parts of yttrium oxide, 1-5 parts of fluoride, 1-3 parts of aluminum isopropoxide, and 10-20 parts of a binder; The binder is a polyvinyl alcohol grafted triazine isocyanate solution; The mass concentration of the polyvinyl alcohol grafted triazine isocyanate solution is 5-10%; The preparation method of the polyvinyl alcohol grafted triazine isocyanate solution is as follows: Dissolve polyvinyl alcohol in DMF, add triazine isocyanate and organotin catalyst, stir and mix, react the obtained reaction solution in a water bath at 40-60°C for 5-10h, remove DMF by vacuum distillation after the reaction, and finally add anhydrous ethanol and mix to obtain a solution of corresponding mass concentration; The mass ratio of the polyvinyl alcohol to the triazine isocyanate is 50-100:

1.

2. The high thermal conductivity silicon nitride ceramic material according to claim 1, characterized in that: The fluoride consists of ammonium fluoride and magnesium fluoride.

3. The high thermal conductivity silicon nitride ceramic material according to claim 2, characterized in that: The mass ratio of ammonium fluoride to magnesium fluoride is 1-5:1-5.

4. A method for preparing a high thermal conductivity silicon nitride ceramic material as claimed in any one of claims 1 to 3, characterized in that: Silicon nitride, magnesium silicon nitride, yttrium oxide and fluoride are mixed and ball-milled, and then dried to obtain a first mixed powder; the first mixed powder is then mixed and ball-milled with aluminum isopropoxide under nitrogen protection, and then dried to obtain a second mixed powder; the second mixed powder is mixed with a binder to form granules; the obtained granules are added to a mold and pressed into a green body; the green body is placed in a sintering furnace, and nitrogen with a pressure of 1-10MPa is introduced for protection; the temperature is first raised to 500-600°C for pre-sintering for 1-5h, and then the temperature is raised to 1500-1700°C for sintering for 1-5h.

5. The method for preparing a high thermal conductivity silicon nitride ceramic material according to claim 4, characterized in that: The speed of the first stage heating is 1-5°C / min, and the speed of the second stage heating is 10-20°C / min.

Citation Information

Patent Citations

  • Method for preparing silicon nitride nanowire-enhanced silicon nitride porous ceramics

    CN103214264A

  • Preparation method of super material substrate and super material antenna

    CN103289274A